Imperfect knowledge and monetary policy - Issing, Otmar (Cambridge, UK ; New York : Cambridge University Press, 2005)
This book discusses the problem of formulating monetary policy in practice, under the uncertain circumstances which characterize the real world. It further explores the implications of a simple model where the policy maker has imperfect knowledge about potential output and the private sector forms expectations according to adaptive learning. The book shows that imperfect knowledge limits the scope for active stabilization policy and strengthens the case for conservation.
Includes bibliographical references (p. 122-135) and index.
nmn 22/05/13
Loans
Keywords: Monetary policy